FAKTOR DETERMINAN PENGUNGKAPAN INFORMASI DAMPAK PANDEMI COVID-19 DALAM LAPORAN KEUANGAN PERUSAHAAN - Khairina Nur Izzaty; Suci Atiningsih (ITB AAS INDONESIA, 2022)
This study aims to find empirical evidence related to the factors that influence th firms to make voluntary disclose information on the impact of Covid-19 pandemic. This research is motivated by the phenomenon of extraordinary event due to the Covid-19 pandemic that hasa hit the world, including Indonesia, which also has an impact on financial and business reporting schemes. The data collection method is secondary sources, consist of financial reports of trading companies, accommodation services, tourism services, transportation services, and other services listed on the Indonesia Stock Exchange in 2020. Furthermore, to analyze the data, logistic regression analysis method is used. The result of the study stated that only the sales growth variable had a significant and negative effect on the disclosure of information on the impact of the Covid-19 pandemic. While other variables, namely profitability, liquidity, market capitalization, foreign ownership, and institutional ownership have no effect on disclosure of information on the impact of the Covid-19 pandemic